A New Approach for the Quantitative Evaluation of the Clock Drawing Test: Preliminary Results on Subjects with Parkinson's Disease - Maria Francesca De Pandis; Manuela Galli; Sara Vimercati; Veronica Cimolin; Maria Vittoria De Angelis; Giorgio Albertini (Neurology Research International)
Aims. The realization of an experimental set-up for the quantitative and objective description of drawing using optoelectronic systems, which could be used when a quantification of the realization of specific drawing tests is required. Methods. Healthy subjects, subjects with Parkinson's Disease and subjects with Parkinson's Disease and Dementia were evaluated by the Mini Mental Scale Evaluation and by a new approach to the Clock Drawing Test, based on an optoelectronic acquisition. The new protocol hereby described aims to define a parameter related to the movement kinematics in the Clock Drawing test execution. Results. The experimental set-up revealed to be valid introducing new objective measurements beside the subjective Clock Drawing Test. This paper suggests the applicability of this protocol to other fields of motor and cognitive valuation, as well as the introduction of new parameters related to the graphic movement.